(untitled) (diségno, 2023)
The aim of this contribution is to demonstrate the exploratory nature of the representation of landscapes from both the more properly expressive and interpretative aspects and the analytical and cognitive one of the environmental contexts. Initially, the paper clarifies the historical and cultural reasons for the link between point of view and landscape, then retracing some historical stages in the alternation between perspective point of view and zenithal point of view in the representation of the landscape. Subsequently, the paper illustrates some research carried out and in progress at the Department of Architecture of the University of Roma Tre concerning methods of acquisition, processing and data management aimed at reading, analyzing and understanding the landscape. The case studies are: representation of the archaeological landscape of the southern sector of Rome; survey and representation of the site where the Mausoleum of Sant’Urbano is located at the IV mile of the via Appia Antica with UAV and laser scanner; survey of the coast of the Pontine-Roman sector.